The Juridical Analysis of the Urgency of Ratifying the Draft Law on Asset Forfeiture in Indonesia - Christian Samuel Lodoe Haga; Netanya Aurora Siwy (PDIH Untag Semarang, 2023)
This research has the purpose of providing a juridical analysis of the urgency of ratifying the asset confiscation law in Indonesia. This article emphasizes normative juridical research with a case study approach, statutory approach, as well as empirical approach to understand the asset confiscation draft law as norms that apply to society. The type of data analyzed in this article are mainly secondary data from the Indonesian law, books, news, previous research, and journals related to money crime and asset confiscation draft law. Previous research found that Indonesia’s corruption Perception Index reached its lowest point of 34 out of 100 last year, indicating that corruption and money crime continue to occur even after a multitude of efforts to combat corrupt practices. Hence, the Indonesian law system requires an extraordinary effort to cope with this extraordinary crime, specifically through the asset confiscation law. Several indicators discovered from this research reveal the urgency of this law. The asset confiscation law would be a solution to the problems of economic crimes in Indonesia through its function as a social control to achieve legal objectives, namely justice.